Towards Interference-Aware Routing for Real-time Traffic in Multi-hop Wireless Networks - Kolar, Vinay; Abu-Ghazaleh, Nael B. (Proceedings of the 11th IEEE International Symposium on Distributed Simulation and Real-Time Applications, 2007)
We formulate the real-time routing problem in static multi-hop wireless networks as an optimization problem, whose solution is the optimal routes relative to an end-to-end delay based objective. The problem is formulated as a mixed integer linear program. The variance of the delay with respect to the aggregate interference measures is empirically studied and a linear approximation is proposed. We show that this formulation yields routes that significantly outperform the best routes obtained by OLSR. Finally, we discuss the applications of such a model both in terms of capacity analysis, on-line algorithms for static scenarios, and extensions to allow the development of distributed protocols that solve the optimization problem.